Population Pharmacokinetic/Pharmacodynamic Modeling of Depot Testosterone Cypionate in Healthy Male Subjects. (1st March 2018) - Bi, Youwei; Perry, Paul J.; Ellerby, Michael; Murry, Daryl J.
Abstract : A randomized, double‐blind clinical trial was conducted to investigate long‐term abuse effects of testosterone cypionate (TC). Thirty‐one healthy men were randomized into a dose group of 100, 250, or 500 mg/wk and received 14 weekly injections of TC. A pharmacokinetic/pharmacodynamic (PK/PD) model was developed to characterize testosterone concentrations and link exposure to change in luteinizing hormone and spermatogenesis following long‐term TC administration. A linear one‐compartment model best described the concentration‐time profile of total testosterone. The population mean estimates for testosterone were 2.6 kL/day for clearance and 14.4 kL for volume of distribution. Weight, albumin, and their changes from baseline were identified as significant covariates for testosterone. The estimated potency of total testosterone (tT) with respect to suppression of luteinizing hormone (LH) synthesis was 9.33 ng/mL. Simulation based on the indirect response model suggests the suppression of endogenous testosterone secretion, LH synthesis, and spermatogenesis was more severe and of greater duration in the 250 mg and the 500 mg dose groups.